The Use of Contemporary Technology to Enhance English Communication Competency (International Journal of Food and Nutritional Sciences, 2022)
A major improvement in today's methods of teaching English is the integration of new technology. Teachers increasingly favour using online courses to instruct their classes since they encourage greater interaction between professors and students and greater English language acquisition overall. Present-day ESL educators are more likely than ever to make use of a variety of technological tools created specifically to enhance lesson delivery. Therefore, the current study focuses on a number of aspects of the technology used in English teaching, including the development of innovative curricula that take advantage of recent scientific and technical developments, the provision of technical media like audio and video and modern technical programmes, and the creation of student-teacher platforms that maximise optimistic language learning outcomes. The goal of this research was to explore the existing literature, provide a linguistic and conventional definition of technology, and assess its correlation with current pedagogical practises. Thus, the researcher presents the research topic, the study aims and hypotheses, and the results. The paper finishes with a series of suggestions that, if implemented, could further contribute to the enhancement of pedagogical practises through the promotion of the wider implementation of contemporary technological tools.